Amenity grassland quality following anaerobic digestate application. (19th June 2018) - Pawlett, Mark; Owen, Andy; Tibbett, Mark
Abstract: Anaerobic digestate applied to land is a source of readily available nutrients, yet there is a paucity of knowledge regarding effects on grassland. To address this, we investigated the viability of using digestate as an alternative to mineral fertilizer for Lolium perenne L. grassland maintenance. We present findings of two independent field‐trials, where food‐waste digestate was applied over two growing seasons at two rates (100 and 200 kg N ha −1  year −1 ) and compared to mineral fertilizer (N:P:K‐12:4:6 at 100 kg N ha −1  year −1 ) and control (no additions) plots. L. perenne nutrition (N, P and K), chlorophyll and sward composition were assessed in the summer and autumn to observe treatment and seasonal effects. The sward benefited from digestate application in the summer with reduced occurrence of dead L. perenne . Both the digestate and mineral fertilizer shifted the sward composition similarly and in favor of Poa annua L. in summer and L. perenne in autumn, with reduced broad‐leaved weeds and bare soil coverage regardless of season. Quantities of foliar N and K uptake were similar between the digestate and mineral fertilizer; however, the highest rate of digestate application was required to supply similar quantities of P to the grass compared to the mineral fertilizer. Grass chlorophyll was not adversely affected by the high ammonium‐N in the digestate. These broadly positive results for digestate present opportunities for the development of digestate use as a fertilizer on amenity grassland such as outfields in sports facilities, parks, and road verges as well as showing potential for supplementing the fertility of pasture systems.